2021
DOI: 10.1111/ced.14809
|View full text |Cite
|
Sign up to set email alerts
|

Anakinra for recalcitrant pyoderma gangrenosum

Abstract: Pyoderma gangrenosum (PG) is an autoinflammatory neutrophilic dermatosis characterized by rapidly enlarging, painful ulcers. Anakinra is a recombinant interleukin (IL)-1 receptor antagonist that blocks the activity of IL-1a and IL-1b by competitively inhibiting IL-1 binding to the IL-1 type 1 receptor. We present a series of two patients with recalcitrant PG, who had limited therapeutic options and multiple comorbidities and multiple previous treatment failures, who obtained 100% healing with anakinra. Compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“… 9 In addition, IL-1 antagonists may be effective in treating recalcitrant PG. 1 O’Connor et al 10 reported 100% healing with anakinra, an IL-1 receptor antagonist that blocks the activity of IL-1α and IL-1β, in 2 patients with multiple comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“… 9 In addition, IL-1 antagonists may be effective in treating recalcitrant PG. 1 O’Connor et al 10 reported 100% healing with anakinra, an IL-1 receptor antagonist that blocks the activity of IL-1α and IL-1β, in 2 patients with multiple comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids can be combined with immunosuppressive or immunomodulating drugs such as colchicine, dapsone, minocycline, apremilast, thalidomide, methotrexate, mycophenolate mofetil, cyclophosphamide, azathioprine, tacrolimus and high‐dose intravenous immunoglobulins 51 . There is increasing evidence of the very good efficacy of different biologics, including anti‐TNF‐α drugs such as infliximab, 52 adalimumab, 53 etanercept, 54 anti‐IL‐12/23: ustekinumab, 55 anti‐IL‐1: anakinra, 56 canakinumab 57 or small molecules like JAK/STAT inhibitors: tofacitinib 58 . A valid treatment approach for severe courses of PG may be an initial combination of systemic drugs and then maintenance of remission with a less toxic regimen of local therapeutics after disease activity is under control.…”
Section: Vasculopathymentioning
confidence: 99%
“…IL‐1 directed treatment with Anakinra and Bermekimab, reached HiSCR in approximately 60%–80% of HS patients in randomized controlled trials 23,24 . Case report data has also demonstrated the successful treatment of both PG and PAPA syndrome with IL‐1 blockade 25,26 22,27 …”
Section: Cutaneousmentioning
confidence: 99%
“…23,24 Case report data has also demonstrated the successful treatment of both PG and PAPA syndrome with IL-1 blockade. 25,26 Use of TNF-α directed therapies (Adalimumab, Infliximab) have also been efficacious in the management of acne, HS, and PG, given overexpression of TNF-α in the lesional skin of both HS and PG. 22,27 IL-17 also plays a critical role alongside IL-1 and TNF-α, in the creation of metalloproteinases by neutrophils which results in extracellular matrix destruction and in further production of inflammatory chemokines.…”
Section: Pyoderma Gangrenosum (Pg)mentioning
confidence: 99%